2021
DOI: 10.1038/s41420-021-00696-6
|View full text |Cite
|
Sign up to set email alerts
|

RCN1 induces sorafenib resistance and malignancy in hepatocellular carcinoma by activating c-MYC signaling via the IRE1α–XBP1s pathway

Abstract: The increasing incidence of hepatocellular carcinoma (HCC) is of great concern globally, but the molecular pathogenesis of these tumors remains unclear. Sorafenib is a first-line drug for the treatment of advanced HCC. However, the efficacy of sorafenib in improving patient survival is limited, and most patients inevitably develop resistance to this drug. Recent studies have demonstrated that the activation of the IRE1α–XBP1s pathway might play a protective role in the response to sorafenib and contribute to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
7
13
0
Order By: Relevance
“…RCN1 has been demonstrated to be highly expressed in a variety of tumor cells and is correlated with patient prognosis in renal cell carcinoma, prostate cancer, glioblastoma, non-small cell lung cancer, oral squamous cell carcinoma, nasopharyngeal cancer, colon cancer, laryngeal cancer, highly aggressive breast cancer, sorafenib-resistant hepatocellular carcinoma cells, and gemcitabine-insensitive human pancreatic adenocarcinoma cells, among others [20][21][22]24,25,27,[55][56][57][58][59][60][61][62][63]. Yoshida et al [64] reported that RCN1 was expressed in lymphatic endothelial cells (T-LECs) and lung cancer cells in lung tumors, but not in lymphatic endothelial cells (N-LECs) in nontumor tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RCN1 has been demonstrated to be highly expressed in a variety of tumor cells and is correlated with patient prognosis in renal cell carcinoma, prostate cancer, glioblastoma, non-small cell lung cancer, oral squamous cell carcinoma, nasopharyngeal cancer, colon cancer, laryngeal cancer, highly aggressive breast cancer, sorafenib-resistant hepatocellular carcinoma cells, and gemcitabine-insensitive human pancreatic adenocarcinoma cells, among others [20][21][22]24,25,27,[55][56][57][58][59][60][61][62][63]. Yoshida et al [64] reported that RCN1 was expressed in lymphatic endothelial cells (T-LECs) and lung cancer cells in lung tumors, but not in lymphatic endothelial cells (N-LECs) in nontumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Reticulocalbin-1 (RCN1), an endoplasmic reticulum protein, plays a crucial role in calcium homeostasis and inhibits ER stress-induced apoptosis [19,20]. In multiple cancers, such as glioblastoma, non-small cell lung cancer, renal cell carcinoma, hepatocellular carcinoma, and oral squamous cell carcinoma, the overexpression of RCN1 has been observed indicating its involvement in tumorigenesis and invasion [21][22][23][24][25]. High levels of RCN1 expression have been associated with sorafenib resistance in hepatocellular carcinoma and doxorubicin resistance in uterine cancer cells [23,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research showed CAFs secreted HGF to upregulate the expression of cell differentiation (CD)-73, and CD73 positive HCC cells were more resistant to the effects of sorafenib and cisplatin [ 18 ]. Additionally, a recent study by our team showed that CAFs can induce the Reticulocalbin 1 (RCN1) expression in HCC, and high-expressing RCN1 can attenuate the sensitivity of HCC cells to sorafenib via the IRE1α-XBP1s pathway [ 48 ]. Apart from that, chemoresistant HCC cells can also promote CAFs functional enhancement, which in turn provides a more favorable microenvironment for HCC cells to survive.…”
Section: The Roles Of Cafs In Hcc Progressionmentioning
confidence: 99%
“…There have been reports of RCN1 protein dysregulation in a variety of diseases, including cardiovascular disease, neuromuscular disease, and tumors (6-8). In recent years, RCN1 has received widespread attention due to its important role in tumorigenesis and progression (9)(10)(11)(12)(13). For example, in prostate cancer cells, downregulation of RCN1 promoted apoptosis and necrosis of cancer cells (13); in non-small cell lung cancer, high expression of the RCN1 protein was found to be signi cantly associated with poor prognosis in non-small cell lung cancer patients, and inhibition of RCN1 was shown to reduce proliferation, migration, and invasion of lung adenocarcinoma cells (12).…”
Section: Introductionmentioning
confidence: 99%